Flt3L therapy increases the abundance of Treg-promoting CCR7+ cDCs in preclinical cancer models - Clappaert, Emile J.; Kancheva, Daliya; Brughmans, Jan; Debraekeleer, Ayla; Bardet, Pauline M. R.; Elkrim, Yvon; Lacroix, Dagmar; Živalj, Maida; Hamouda, Ahmed E.I.; Van Ginderachter, Jo A.; Deschoemaeker, Sofie; Laoui, Damya (Frontiers in Immunology, 2023)
Conventional dendritic cells (cDCs) are at the forefront of activating the immune system to mount an anti-tumor immune response. Flt3L is a cytokine required for DC development that can increase DC abundance in the tumor when administered therapeutically. However, the impact of Flt3L on the phenotype of distinct cDC subsets in the tumor microenvironment is still largely undetermined. Here, using multi-omic single-cell analysis, we show that Flt3L therapy increases all cDC subsets in orthotopic E0771 and TS/A breast cancer and LLC lung cancer models, but this did not result in a reduction of tumor growth in any of the models. Interestingly, a CD81+migcDC1 population, likely developing from cDC1, was induced upon Flt3L treatment in E0771 tumors as well as in TS/A breast and LLC lung tumors. This CD81+migcDC1 subset is characterized by the expression of both canonical cDC1 markers as well as migratory cDC activation and regulatory markers and displayed a Treg-inducing potential. To shift the cDC phenotype towards a T-cell stimulatory phenotype, CD40 agonist therapy was administered to E0771 tumor-bearing mice in combination with Flt3L. However, while αCD40 reduced tumor growth, Flt3L failed to improve the therapeutic response to αCD40 therapy. Interestingly, Flt3L+αCD40 combination therapy increased the abundance of Treg-promoting CD81+migcDC1. Nonetheless, while Treg-depletion and αCD40 therapy were synergistic, the addition of Flt3L to this combination did not result in any added benefit. Overall, these results indicate that merely increasing cDCs in the tumor by Flt3L treatment cannot improve anti-tumor responses and therefore might not be beneficial for the treatment of cancer, though could still be of use to increase cDC numbers for autologous DC-therapy.